Factors Related to Health Toilet Ownership in The Working Area of Luas Health Center in Kaur Regency - Mike Milo Diana Putri; Julius Habibi; Retni Retni (Journal of International Public Health, 2026)
Intoduction: A healthy toilet is a waste disposal facility that prevents contact between humans and feces, makes the feces impermeable to insects and other animals, prevents contamination of water bodies, and prevents unpleasant odors. The seat is well- constructed, safe, and easy to clean (Lamentira, 2020). Based on data from the Working Area of Luas Health Center in Kaur Regency, out of 12 villages, four villages have not yet achieved Open Defecation Free (ODF) or Stop Open Defecation, with a population of 610 families (Luas Health Center, 2024). This study aims to determine the ownership of healthy toilets in the the Working Area of Luas Health Center in Kaur Regency in 2025. Method: The method used in this study was a survey method with a cross-sectional approach. The research sample consisted of 86 respondents. Data analysis was performed using a chi-square test with a 95% significance level using SPSS 22 software.. Result and Discussion: Univariate analysis results showed that 76 (88.4%) respondents had low incomes, 47 (54.7%) had sufficient knowledge, 49 (57.0%) had unsupportive attitudes, and 49 (57.0%) had access to healthy latrines. Bivariate analysis results showed a significant correlation between income (p value) = 0.010, knowledge (p value) = 0.021, and attitude (p value) = 0.017) and access to healthy latrines in the Working Area of Luas Health Center in Kaur Regency in 2025 (α < 0.05). Conclusion: This study aims to improve health promotion efforts, environmental sanitation program planning, and evaluate the effectiveness of implemented activities to promote clean and healthy living behaviors in the community.